Proceedings of the 18th Brazilian Symposium on Multimedia and the Web 2012
DOI: 10.1145/2382636.2382655
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of the social network on marking photos as favorites in flickr

Abstract: Understanding user behavior in user generated-contend systems (UGCs) is a fundamental building block for maximizing usefulness of these systems. For example, the importance of users' connections and the degree of iteration is needed in order to build meaningful recommendation systems. In this paper, we evaluate the impact of users' network on marking photos as favorites in Flickr considering various levels of distance between users in the network topology. We have observed that users' first-degree contacts are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Few libraries like the Auburn University Library used Flickr for the library photostream. Flickr is an image-hosting service that enabled users to upload their pictures, have them automatically resized and given a unique URL, and displayed on the web for all to see (Alves et al, 2012). Flickr also allows a contacts list to keep track of your buddies and friends.…”
Section: Resultsmentioning
confidence: 99%
“…Few libraries like the Auburn University Library used Flickr for the library photostream. Flickr is an image-hosting service that enabled users to upload their pictures, have them automatically resized and given a unique URL, and displayed on the web for all to see (Alves et al, 2012). Flickr also allows a contacts list to keep track of your buddies and friends.…”
Section: Resultsmentioning
confidence: 99%
“…They found that 50% of the favorite actions occurred within one week of an image’s upload date, and the largest portion of these favorites was from the owner’s contacts. Alves et al, in [18], studied the impact of users’ networks on favorite actions on Flickr. They reported that 70% of the favorite marks of photos were received from the owner’s contacts.…”
Section: Related Workmentioning
confidence: 99%
“…Nos dias atuais, redes sociais online são um importante meio de entretenimento, interação e comunicação entre pessoas em todo o mundo. A atuação das pessoas nessas redes tem sido objeto de estudo em diversas perspectivas [Ellison et al 2007, Alves et al 2012, Figueiredo et al 2014. Entre as principais redes sociais atualmente estão o Facebook, Instagram, Flickr e o Twitter.…”
Section: Introductionunclassified